PELATIHAN INTERNET OF THINGS MENGGUNAKAN ARDUINO UNO UNTUK MENINGKATKAN KETERAMPILAN GURU - Ikhsan Fakhri Fadillah; Fitroh Anugrah Kusuma Yuhda; Bambang Riyanta; Nur Ardiyansyah; Aditya Kurniawan (Jurnal Abdimas Bina Bangsa, 2023)
Community service activities have been carried out with the topic of Internet of things training using Arduino Uno to improve teacher skills. The Service Partner is SMK Muhammadiyah 3 Yogyakarta. The targets of this service are vocational teachers from the Light Vehicle Engineering, Mechanical Engineering, Audio Video Engineering, Electrical Installation Engineering, and Computer Network Engineering expertise programs. The purpose of this activity is to increase the knowledge of teacher participants about technological developments, especially the Internet of things which is currently developing in the current technological era. The learning materials presented are the basic concepts of the Internet of things, programming languages, introduction to hardware and software components (Arduino IDE and Blynk), and the application of the Internet of things in the industrial world and everyday life. The results of the training showed that the participants experienced an increase in score of 79.12% based on the initial exam average score of 45.5 and the final average score of 81.5